2005
DOI: 10.1093/bjsw/bch297
|View full text |Cite
|
Sign up to set email alerts
|

Parents Whose Children with Learning Disabilities and Challenging Behaviour Attend 52-week Residential Schools: Their Perceptions of Services Received and Expectations of the Future

Abstract: Peter McGill is Senior Lecturer in Learning Disability at the Tizard Centre. A clinical psychologist by training, he has previously held posts in the NHS, Social Services and the Voluntary sector. Alan Tennyson is a Programme Supervisor with the RehabCare Group. He carried out this research during postgraduate study at the Tizard Centre. Vivien Cooper is the parent of a young man with severe learning disabilities and challenging behaviour and the founder of the Challenging Behaviour Foundation, an organisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 14 publications
1
60
1
Order By: Relevance
“…In extreme cases the child may have to move to high-cost residential placements (McGill et al, 2006). A more cost-effective approach is the provision of family support services.…”
Section: Introductionmentioning
confidence: 99%
“…In extreme cases the child may have to move to high-cost residential placements (McGill et al, 2006). A more cost-effective approach is the provision of family support services.…”
Section: Introductionmentioning
confidence: 99%
“…This would lead to the segregation of students with MSID into residential schools (McGill, Tennyson, & Cooper, 2006;Roberts & Ridley, 2009). This (albeit unlikely pathway in the Australian context) would lead to all students with MSID being placed in residential schools wherein a '24/7 IEP' would be implemented across 'controlled' school, home and community settings.…”
Section: Assessmentmentioning
confidence: 99%
“…This (albeit unlikely pathway in the Australian context) would lead to all students with MSID being placed in residential schools wherein a '24/7 IEP' would be implemented across 'controlled' school, home and community settings. Clearly there would be widely opposing philosophical, ethical, pedagogical and pragmatic views on '24/7 IEPs' for students with MSID in Australia notwithstanding that residential schools are quite common in many other countries and an emerging trend in Great Britain is to support these placements 'in the best interests' of the students and their families (McGill et al, 2006). In this pathway, the main variables are placement and pedagogy, although curriculum and assessment might remain essentially the same.…”
Section: Assessmentmentioning
confidence: 99%
“…However, concerns have been raised around professionals being unable to make sense of the situation and therefore unable to offer the most appropriate support as they may misunderstand the complexity of the mothering role (Edelson 2000). One study, investigating the perceptions of parents of children attending residential schools, revealed considerable dissatisfaction with the support and services available prior to the residential option being sought (McGill, Tennyson, and Cooper 2006). These authors also reported high rates of exclusion from local services and elevated levels of concern about the future, indicating the fundamental uncertainty instigated by the child's additional behaviour problems.…”
Section: Professional Supportmentioning
confidence: 99%